PRODUKSI MASSAL AGENS HAYATI Pseudomonad fluoresen MENGGUNAKAN MEDIUM AIR KELAPA - Advinda, Linda (IAIN Batusangkar, 2010)
This research had been done to know the mass production of Pf (Fluorescent Pseudomonads) in coconut liquid media. Randomized Complete Design (RCD) with 5 treatments and 3 replications was implemented in this research which consisted of 5 incubation periods: the 0, 2nd, 4th, 6th, and 8thweeks. The data gathered were analyzed by ANOVA and DNMRT (5% confidence level). As the result, the incubation period within 6 weeks in coconut liquid media gave good response to increase the mass production of Pf. On the other hand, the incubation period within 8 weeks gave bad response.Key words: Pseudomonad fluoresen, mass production, coconut liquid